ANALYSIS OF PACKAGING PRINT QUALITY WITH CTF AND CTCP PLATE MAKING SYSTEMS USING DUPLEX PAPER MATERIALS - Roni Fransiscus Lumbantoruan; Septia Ardiani; Untung Basuki (Politeknik Negeri Media Kreatif, 2021)
Comparative analysis of packaging print quality was carried out on the printed output with reference to using Computer to Film (CtF) and Computer to Conventional Plate (CtCP). The comparison of the print results from the two systems is analyzed from cost, durability, and dot gain. In this analysis, 400 gram duplex paper was used and two types of print references were used, namely CtF and CtCP. The pre-printing equipment used is the manufacture of conventional printing plates and plates. What is achieved when observing is comparing two print references with the help of a quality control (QC) tool. Before comparing the two print references, direct printing is done with the two print references, using an offset machine. The differences that exist in CtF and CtCP are caused by different irradiation processes. CtF goes through two irradiation processes while CtCP is in the irradiation process using only lasers. The irradiation process using a laser is uneven and makes the plate not get a raster (neat) result. This process is very influential with the result of the trigger. CtF goes through an iterative process but the results appear better than CtCP.Keywords— Print packaging, Duplex, CtF, CtCp